Pemikiran Abed Al-Jabiri Terhadap Nalar Arab: Konsep dan Relevansi - Yandi Hafizallah; Muhammad Abdul Wafa (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
This paper aims to explain and analyze the epistemological aspects based on the thoughts of Abed al-Jabiri, especially regarding the thinking of three Arabic reasoning of al-Jabiri. The study refers to three thoughts of Arabic al-Jabiri reasoning about epistemology namely: